Mid-Winter Breakout of Landfast Sea Ice and Major Storm Leads to Significant Ice Push Event Along Chukchi Sea Coastline - Bogardus, Reyce; Maio, Christopher; Mason, Owen; Buzard, Richard; Mahoney, Andrew; de Wit, Cary (Frontiers in Earth Science, 2020)
During the winter of 2016, anomalous sea ice conditions and a powerful storm culminated in a destructive erosion event along the Chukchi Sea coastline of Cape Espenberg, Alaska. This event is commonly referred to as an "ice push" or "ivu,” the Inupiat word for an ice ridging event. In this paper we report the process and impact of this event by combining traditional ecological knowledge, news accounts, meteorological data, remote sensing, and ground surveys. The mid-winter detachment of shorefast ice was caused by a low-pressure system and wind-driven swell that destabilized shorefast ice, while northerly winds developed an open-water lead offshore to the eventual impact area. These conditions preceded the impact of an extratropical cyclone on December 31, 2016, when powerful southerly winds and the second largest storm surge in Kotzebue Sound since at least 2003 led to the compressional failure of the ice cover under uni-axial loading perpendicular to the southern coastline of the Cape, resulting in the ice push event. Ice-pushed debris were shoved up to 6.2 m above mean high water, with ~3.5 km of coastline experiencing net erosion. The largest accumulation of ice-pushed debris had a volume of 1,000 m3, and rose 3+ m above the surrounding ground surface even after roughly 6 months of melting. On low-lying areas, driftwood and other debris were deposited 130 m landward by the surge 5.0 m above mean high water, indicating the potential threat of such events to property, infrastructure and, in this case, archeological sites and associated cultural resources. The anomalous environmental and sea ice conditions that preceded the ivu, seem to suggest that such events may occur more frequently in a warmer Arctic.